2020
DOI: 10.1007/s11239-020-02288-0
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for intracerebral hemorrhage in patients with COVID-19

Abstract: Intracerebral hemorrhage (ICH) can be a devastating complication of coronavirus disease (COVID-19). We aimed to assess risk factors associated with ICH in this population. We performed a retrospective cohort study of adult patients admitted to NYU Langone Health system between March 1 and April 27 2020 with a positive nasopharyngeal swab polymerase chain reaction test result and presence of primary nontraumatic intracranial hemorrhage or hemorrhagic conversion of ischemic stroke on neuroimaging. Patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
72
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(79 citation statements)
references
References 41 publications
5
72
2
Order By: Relevance
“…It has been shown that ICH in COVID-19 could be linked with anticoagulation treatment. More than half of these patients were on anticoagulation due to significantly high D-dimer levels, and a larger number of ICH patients were on heparin (treatment dose) ( Melmed et al., 2020 ). It is speculated that could be rather a sign of severity of the illness than the increased risk of ICH while on heparin infusion ( Melmed et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that ICH in COVID-19 could be linked with anticoagulation treatment. More than half of these patients were on anticoagulation due to significantly high D-dimer levels, and a larger number of ICH patients were on heparin (treatment dose) ( Melmed et al., 2020 ). It is speculated that could be rather a sign of severity of the illness than the increased risk of ICH while on heparin infusion ( Melmed et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…5 New York University Langone Hospitals, New York, NY, USA. 6 Department of Population Health, New York University Grossman School of Medicine, New York, NY, USA.…”
Section: Supplementary Informationmentioning
confidence: 99%
“…Multiple studies have identified neurological events in the context of recent severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection [1][2][3][4][5][6][7][8]. Many of these complications are sequelae of severe illness or represent secondary effects of multisystem organ failure.…”
Section: Introductionmentioning
confidence: 99%
“…43 This is not to say that anticoagulation is appropriate for all stroke patients, particularly given that anticoagulation was identified as an independent risk factor for intracranial hemorrhage in patients with COVID-19. 51 Instead, it highlights the need to direct future studies at evaluating the role of anticoagulants in treating acute ischemic strokes in COVID-19-positive patients who are not eligible for currently recommended therapies (eg, recombinant tissue plasminogen activator (rtPA) or thrombectomy). Gavioli et al have published a proposed clinical treatment pathway for hospitalized COVID-19 patients which guides treatment with prophylactic versus therapeutic heparin and enoxaparin as well as rtPA in hospitalized patients with COVID-19.…”
Section: Basic Sciencementioning
confidence: 99%